Advanced Zeolite Composites with Nzvi for Lead Removal in Mining Water: Laboratory Results and Field Validation - Rubio-Campos, M; Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (Springer Nature, 2025)
nZVI-functionalized zeolites were synthesized and characterized at two coating percentages: 25% (C1) and 50% (C2) w/w using FT-IR, XRD, SEM, and EM. XRD confirmed nZVI formation in the composite while SEM revealed smaller nZVI size on zeolite surfaces (C1 = 45 nm, C2 = 64 nm) than on pristine nZVI (77 nm). Pb2+ sorption was assessed on in situ synthesized nZVI-functionalized zeolites alongside the presence of the competing cation Al3+. Sorption studies showed a 60-min equilibration time for Pb2+ in composites. Pb2+ removal capacity was higher in composites than in pristine materials despite a marked decrease caused by the presence of Al3+. Composites maintained a preference for Pb2+ sorption over Al3+. The Langmuir model fits experimental data well, indicating higher Fe content in materials and increased sorption capacity and intensity for Al3+ when both cations coexisted. Nevertheless, the obtained material exhibited excellent qualities for Pb2+ removal, even in the presence of a competing element like Al3+. In addition, the water-tested materials were used in a copper mining site, which contains high concentrations of both metals. The materials displayed a similar trend to the laboratory tests, confirming their performance in complex systems, such as the water generated in mining processes. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.